2005
DOI: 10.1111/j.1469-0691.2004.01039.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an amikacin-resistant Escherichia coli strain after tobramycin treatment of previous recurrent episodes of respiratory tract infections caused by Pseudomonas aeruginosa

Abstract: Amikacin-resistant Escherichia coli strains are isolated rarely from clinical samples. In the present study, investigation of an amikacin-resistant clinical isolate of E. coli demonstrated the presence of two class 1 integrons carrying the aacA4 gene plus the aacA7 gene, and the dfrA17 gene plus the aadA5 gene, respectively. Resistance to amikacin in this E. coli isolate was related to the presence of both aacA4 and aacA7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Overall, it seems that the presence of both adenylyltransferase ( aadA ) and acetyltransferase ( aacA4 ) is essential for amikacin resistance. Previous studies related amikacin resistance in E. coli to the presence of aacA4 and aacA7 together [ 40 ]; along the same lines with our finding, it was reported that the ANT(3″) enzymes confer more resistance against amikacin in Serratia marcescens by increasing the affinity of the aminoglycoside to bind AAC(6′) enzyme [ 41 ]. Only one isolate (1/18) was integron I-negative and aacA4 -positive, and it showed resistance to amikacin; in this isolate, other mechanisms could play a role in such resistance.…”
Section: Discussionsupporting
confidence: 89%
“…Overall, it seems that the presence of both adenylyltransferase ( aadA ) and acetyltransferase ( aacA4 ) is essential for amikacin resistance. Previous studies related amikacin resistance in E. coli to the presence of aacA4 and aacA7 together [ 40 ]; along the same lines with our finding, it was reported that the ANT(3″) enzymes confer more resistance against amikacin in Serratia marcescens by increasing the affinity of the aminoglycoside to bind AAC(6′) enzyme [ 41 ]. Only one isolate (1/18) was integron I-negative and aacA4 -positive, and it showed resistance to amikacin; in this isolate, other mechanisms could play a role in such resistance.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, the resistance of amikacin against most aminoglycoside-modifying genes is commonly reported (as reviewed in [ 81 ]). Notably, amikacin resistance is reported to be mediated by aminoglycoside genes such as aphA6 [ 82 ], armA [ 83 ], aacA4 and aacA7 [ 84 ], none of which were detected in the Segamat cohort.…”
Section: Discussionmentioning
confidence: 99%
“…These results were agreed with Niranjan and Malini who found the isolates of this bacteria were sensitive to this antibiotic (Niranjan and Malini., 2014). But in study of Ruiz et al who found some isolates of this bacteria were resistant to this antibiotic (Ruiz et al, 2005). The current study explained the (Bacitracin) antibiotic has low activity against Escherichia coli.…”
Section: Discussionmentioning
confidence: 53%